The Distribution, Population Size, and Habitat Preferences of a Newly Established Population of the Oriental Magpie Pica serica in Tomakomai City, Hokkaido, Northern Japan - Masahiro Fujioka; Hisaya Murayama (Birds)
Non-native species have caused various problems for both animal and human communities globally, but their monitoring during the early stages of establishment is often difficult. A population of the Oriental Magpie (Pica serica) has established on Hokkaido Island, northern Japan, since the 1990s, offering a rare opportunity for field biologists to monitor the entire history of a colonizing avian population. To clarify the current number and distribution of the population and their major determinants, we conducted bimonthly surveys from May 2012 to March 2013, over a total of 417 h, in Tomakomai City, the central area of the current distribution. We found 181 to 248 magpies in every survey, and 46 active nests in May. Most of the magpies appeared in residential areas, avoiding commercial and industrial areas, and did not show seasonal changes in their distribution pattern. The magpies mainly foraged in short grasslands in public spaces, such as parks, in May and July, but most of the birds preferred house gardens for foraging from November to March. Dogs or cats were often kept outside in the gardens where the magpies foraged, and observations of magpies stealing and hoarding pet food were common. It is likely that the magpies rely on anthropogenic food resources such as pet food, especially in winter. Continuous monitoring of this population will enable further knowledge of the factors that limit the number and range of not only non-native species but also avian populations in general to be obtained.